Incidence of Various Types of Varicose Veins in Relation to Age and Gender Among Patients Presenting in Mayo Hospital - M. Usama Shabbir, Mohammad Akmal Shafiq, Amber Salman, Ahmad Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Amongst the most frequent illnesses in civilised nations of West is chronic venous insufficiency (CVI). It is believed that 40-50 percent of all individuals have superficial venous insufficiency of the leg, which manifests primarily as varicose veins. Individuals with varicose veins typically complain of leg pain at the conclusion of the day following extended walking. Ankle edoema, itch, hemorrhage, superficial thrombophelibitis, dermatitis, lipodermatosclerosis, and open wounds are some of the additional manifestations. Methods: In this cross sectional study, conducted at the surgical floor, Mayo Hospital, Lahore. Varicose veins were defined as dilated, tortuous, subcutaneous veins usually seen in upright posture. Any case of suspected chronic venous insufficiency was assessed on clinical examination by unbiased consultant surgeon. The severity of varicose vein was assessed by clinical grading from CEAP (Clinical-Etiological-Anatomical-Pathophysiological) system in which there are six classes. Results: Patients in our study were mostly males; male to female ratio of patients of varicose veins is 3:1, most of the male patients had class 2 or class 5; Association of class of varicose veins and gender was also insignificant (p-value calculated for the class of varicose veins and gender was 0.25). Conclusion: In our study population, male patients suffered worse than female patients. The occurrence rate was comparable between people of different ages. There was a higher prevalence of varicose veins in classes 2 and 3. To further understand the causes of varicose veins, larger-scale studies focusing on female gender-related risk factors and occupation-related risk factors are needed. Additional measures, such as patient education, can aid in lowering the frequency of varicose veins. Keywords: Varicose Veins, DVTs, Ankle edema, Thrombophelibitis, lipodermatosclerosis